Production and perception of English Word Final Stops By Malay Speakers - Shahidi , A.H.; Rahim Aman,; Ab.Samad Kechot, (Penerbit UKM, 2012)
A few influential speech studies have been carried out using established speech learning models, which confirmed that the analysis of first language (L1) and second language (L2) at a phonemic level provides only a partial view of deeper relationships between languages in contact. Therefore, studies focusing on cross-language phonetic differences as a causative factor in L2 learner difficulties have been proposed to understand second language learners’ (L2) speech production and how listeners respond perceptually to the phonetic properties of L2. This paper presents a study of the production and perception of the final stops by English learners (L2) whose first language is Malay (L1). A total of 23 students, comprising 16 male and 7 female Malay subjects (L1 as Malay and their L2 as English) with normal hearing and speech development participated in this study. A short interview was conducted in order to gain background information about information about each subject, to introduce them to the study, to inform them about the process of recording, the materials to be used in the recording session, and how the materials should be managed during recording time. Acoustic measurements of selected segments occurring in word final positions (via spectrographic analysis, syllable rhyme duration and phonation) were taken. Results of the voicing contrast realisation in Malay accented English and Malaysian listeners' perceptual identification/discrimination abilities with final voiced/voiceless stops in Malay and English are presented and discussed. The findings revealed that the Malay students’ realisation of final stops in L2 is largely identical to their L1. In addition, the results also showed that accurate ‘perception’ may not always lead to accurate ‘production’.